Language and speech naturalistic intervention with late talkers´ families: effects on child language and adult exchanges - Moreno, Rebeca; Nieva, Silvia (Revista de Investigación en Logopedia, 2021)
The aim of this article is to assess the effectiveness of a naturalistic Speech and Language Therapy program. 16 Spanish monolingual families, whose children were between 24 and 29 months old and showed early difficulties in language development, were selected and, subsequently, assigned to two experimental conditions (intervention and control). The families belonging to intervention group benefited from a naturalistic intervention program in which family routines were used to stimulate children´s communicative and linguistic development and to develop conversational order to be adjusted to the level of children´s communicative and linguistic development. With the control group a “wait and see” strategy was used. After 4 months of intervention results reported that the families of the intervention group used more adjusted behaviors and their children showed a more extensive vocabulary and produced more combinations of words compared to the control group.